Comparing frequency and maximum principal strain of head impacts for U15 ice hockey leagues with standard and modified body contact rules - Krbavac, B. P.; Cutler, J.; Lowther, S.; Karton, C.; Post, A.; Robidoux, M.; Gilchrist, M. D.; Hoshizaki, T. B. (Journal of Biomechanics, 2024)
Brain trauma in bodychecking ice hockey is of concern for youth participants, as it presents unique risks compared to the non-bodychecking version of the sport. This study compared head impact frequency and magnitude between two ice hockey leagues with different body contact rules in the U15 age division: AAA (standard bodychecking) and M15 Minor (modified body contact rules). Video analysis of 16 games per league revealed no significant overall diference in impact frequency. M15 Minor players sustained significantly more head-to-head (14 to 2) impacts and AAA players sustained significantly more head-to-glass (18 to 7) and punch impacts (4 to 0). Laboratory reconstructions and finite element modeling were used to determine impact magnitude as maximum principal strain (MPS) and categorized from very low to very high. Higher impact frequency of very low MPS head impact events were observed for M15 Minor (61 to 51). The findings from this study highlight that this method of modifying body contact rules in U15 hockey did not result in lower levels of brain trauma, rather it presented unique brain trauma mechanisms compared to bodychecking.